MAT2A-Mediated S-Adenosylmethionine Level in CD4+ T Cells Regulates HIV-1 Latent Infection - Yang, Xiaofan; Huang, Ting; Wang, Tiantian; Gao, Hongbo; Zhang, Haitao; Peng, Wen; Zhao, Jiacong; Hu, Shujing; Lu, Panpan; Hong, Zhongsi; Li, Bo; Deng, Kai (Frontiers in Immunology, 2021)
Antiretroviral drugs effectively halt HIV-1 replication and disease progression, however, due to the presence of a stable viral latent reservoir, the infection cannot be cured by antiretroviral drugs alone. Elucidating the molecular mechanisms underlying HIV-1 latent infection remains a critical hurdle that precludes the development of novel therapeutic strategies aiming for a potential functional cure. Cellular metabolism has been reported to affect HIV-1 replication in CD4+ T cells, but it remains largely unclear whether it is involved in the regulation of HIV-1 latency. Here, we performed a sub-pooled CRISPR library knockout screen targeting 1773 metabolic-related genes in a cell model of HIV-1 latent infection and found that Methionine Adenosyltransferase 2A (MAT2A) contributes to HIV-1 latency. MAT2A knockout enhanced the reactivation of latent HIV-1 while MAT2A overexpression did the opposite. Mechanistically, MAT2A modulates HIV-1 latency through S-Adenosylmethionine (SAM)-mediated one-carbon flux. MAT2A knockout resulted in a significant downregulation of DNA and histone methylation at the HIV-1 5’-LTR. Importantly, we found that the plasma level of SAM is positively correlated with HIV-1 DNA in PBMCs from ART-treated infected individuals, suggesting SAM could serve as a potential biomarker for the latent viral reservoir. Overall, this study reveals an important role of MAT2A-mediated one-carbon metabolism in regulating HIV-1 latency and provides a promising target for the development of new strategies for a functional cure of HIV-1.